Answer:
12
Step-by-step explanation:
.......................
Answer:
2x + 3y = 12
Step-by-step explanation:
Standard form is Ax + By = C, A, B and C must be intergers, cannot be fractions or decimals
y = -2/3x + 4 First we want to get rid of the fractions. There is only one, so if we multiply both sides by 3 that should do it.
3y = -2x + 12 Now make the constant be on one side by itself
2x + 3y = 12
3 ft – 7 inches to decimal feet. Record your answer to the nearest hundredth of a foot.
rounded 2.42 ft
Answer:
Bbsvsgdv
Step-by-step explanation:
Bsbzvevv
Step-by-step explanation:
Y is directly proportional to X" can be rewritten as a mathematical expression of the form Y = KX
"K" is the constant of proportionality and must be determined from the initial information.
If Y = 2/3 when X=1/12means 2/3=1/12
K = 2/3÷1/12 = 8
Now that we know the value of K, we can use it to calculate the value of Y when X=1/2
Y = (8)(1/2) = 8/2=4
Y=4